A novel method for measuring pulmonary artery pressure by high-frequency ultrasound-guided transthoracic puncture in rats - Zhang, Xiaofeng; Li, Jingtao; Zeng, Decai; Liang, Chunting; Zhong, Yanfen; Huang, Tongtong; Mo, Yingying; Rao, Huaqing; Pan, Xiaoxiong; Wu, Ji (Frontiers in Cardiovascular Medicine, 2022)
Abstract Objectives: Pulmonary artery pressure measurement is key to verifying the success of the rat model of pulmonary hypertension. We herein demonstrate a novel method for measuring pulmonary artery pressure through high-frequency ultrasound-guided transthoracic puncture in rats. The efficacy and time of this novel method are also discussed. Methods: A single subcutaneous injection of monocrotaline (MCT) was used to establish a rat model of pulmonary hypertension. The tip of that puncture cannula was maintained at a certain angle after the needle core was removed through heat shaping method. In the short-axis section of the parasternal aorta, in-plane real-time guided trocar puncture of the right ventricular outflow tract was performed. The external pressure sensor was used to record the real-time waveform, right ventricular systolic pressure, pulmonary artery systolic pressure, and diastolic pressure. Results: The success rates of which using this novel method in the model group and the control group were 88.5% and 86.7%, respectively, and the puncture pressure measurement time was 164±31s and 235±50s, respectively. The model group's right ventricular systolic blood pressure, pulmonary systolic blood pressure, and diastolic blood pressure were higher than those in the control group. Conclusions: The modified method for trocar is helpful for accurately positioning pulmonary artery manometry. The method described in this paper has a high success rate and short operation time. It can simultaneously measure systolic blood pressure, diastolic blood pressure, and mean pressure of the right ventricle and pulmonary artery. It has a broad application prospect in verifying the rat pulmonary hypertension model and pulmonary artery pressure monitoring.